Creativity and Digitalization in Apam Barabai MSMEs: Strategies to Enhance Competitiveness - Burhannudin, Burhannudin; Muhammad Ihsan Maulani; Sri Rahayu (Jurnal Ilmu Manajemen dan Bisnis, 2026)
This study investigates the marketing strategies of Apam Barabai micro, small, and medium enterprises (MSMEs), focusing on the integration of product creativity and digitalization to enhance business competitiveness. Employing a qualitative descriptive approach, data were collected through semi-structured interviews, participatory observation, and documentation involving MSME owners actively engaged in production, marketing, and business management in Hulu Sungai Tengah Regency, South Kalimantan, Indonesia. The findings reveal that Apam Barabai MSMEs predominantly rely on traditional marketing strategies, emphasizing strategic stall locations along busy routes, direct interaction with consumers, and fostering customer loyalty through personalized purchasing experiences. The use of banana leaf packaging preserves product freshness, reinforces cultural identity, and provides aesthetic value, yet remains underutilized in digital promotions. Digital marketing and e-commerce adoption are limited due to insufficient digital literacy and concerns over order management, constraining broader market reach. The study highlights that integrating product innovation—such as packaging, presentation, and flavor variations—with digital platforms can expand market coverage, strengthen brand awareness, and maintain the authenticity of local cuisine. Creative strategies combined with social media and e-commerce utilization present opportunities for MSMEs to increase sales, enhance competitiveness, and sustain customer loyalty. This research contributes to the literature by demonstrating the complementary role of traditional marketing practices and digital tools in local culinary MSMEs, offering practical recommendations for optimizing digital marketing, fostering product innovation, and improving digital skills. The study underscores that strategic location, personalized interaction, product creativity, and digitalization collectively form a robust framework for MSME growth in a digital economy, aligning with modern marketing theory.